A COMPUTATIONAL STUDY OF PARA SUBSTITUENT EFFECTS ON CORROSION INHIBITOR ABILITY OF SELENOCARBAMATES - Hương, Đinh Quý; Dương, Trần; Nam, Phạm Cẩm (Hue University Journal of Science: Natural Science, 2017)
A theorical study of structures and thermochemical properties of Se-methyl-N-phenylselenocarbamate (HM) and nine derivatives, used as corrosion inhibitors in the gas phase was undertaken using Density Functional Theory (DFT) at the B3LYP/6-31G(d) method. Electronic parameters relevant to their inhibition activity such as EHOMO, ELUMO, Energy gap (ΔEL-H), hardness (η), softness (S), the absolute electronegativity (χ), the fraction of electrons transferred from the inhibitor molecule to the metallic atom (ΔN) and Mulliken population analysis were computed and discussed. The results revealed that Se-methyl-N-(4-methylphenyl)selenocarbamate (CH3-M) is the best corrosion inhibitor among nine selenocarbamate derivatives. In addition, computational study also shows that substituents effect geometric parameters of molecular such as bond lengths, bond angles.